Pengaruh Brand Image dan Promosi Gojek Terhadap Keputusan Pengguna Jasa Transportasi Berbasis Online (Studi Pada Mahasiswa Fakultas Ekonomi di Universitas Hasyim Asy’ari Tebuireng Jombang) - Achmad Septigo (BIMA : Journal of Business and Innovation Management, 2021)
This study aims to determine the brand image and promotion of the decision of users of online-based transportation service studies in the students of the faculty of Economics, Tebuireng Jombang. The Method used in this research is quantitative research methods and uses purposive sampling technique. This study uses a sample of 100 people who have made decisions on the use of Gojek Services. This studiy uses multiple linear regression analysis. The testing technique in this study is the validity and reability test, while the data analiysis technique uses the classic assumption test (normality test, heteroscedasticity, multicollinearity, autocorrelation,linearity), while the hypothesis test is the t test, F test and coefficient of determination. The Results showed that brand image and promotion influence user decision.